2006
DOI: 10.1016/j.geomorph.2005.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal rockfall activity in a forest stand in the Swiss Prealps—A dendrogeomorphological case study

Abstract: Rockfall is a major threat to settlements and transportation routes in large parts of the Alps. While protective forest stands in many locations undoubtedly reduce rockfall risk, little is known about the exact frequency and spatial distribution of rockfall activity in a given place or about how these parameters can be assessed. Therefore, the objective of the present study was to reconstruct rockfall events with dendrogeomorphological methods and to analyse the spatial and temporal rockfall activity in a suba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
2
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(93 citation statements)
references
References 39 publications
6
77
2
8
Order By: Relevance
“…In contrast to other mass-movement processes (e.g., Shroder, 1980;Braam et al, 1987;Wiles et al, 1996;Solomina, 2002), tree-ring analyses have only occasionally been 204 D. M. Schneuwly and M. Stoffel: Tree-ring based reconstruction of rockfall in the Swiss Alps used to study past rockfall activity, mainly to determine sedimentation rates on scree slopes (Lafortune et al, 1997) or to reconstruct rates or the spatial occurrence of rockfall (Stoffel et al, 2005a;Perret et al, 2006).…”
Section: Ormentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to other mass-movement processes (e.g., Shroder, 1980;Braam et al, 1987;Wiles et al, 1996;Solomina, 2002), tree-ring analyses have only occasionally been 204 D. M. Schneuwly and M. Stoffel: Tree-ring based reconstruction of rockfall in the Swiss Alps used to study past rockfall activity, mainly to determine sedimentation rates on scree slopes (Lafortune et al, 1997) or to reconstruct rates or the spatial occurrence of rockfall (Stoffel et al, 2005a;Perret et al, 2006).…”
Section: Ormentioning
confidence: 99%
“…While callus tissue only occurs in the wood segment bordering the injury (Stoffel et al, 2005a, b;Perret et al, 2006), TRD can be even observed at some distance from the wound as well (Bollschweiler et al, 2007a;. Bollschweiler et al (2008) indicate a mean lateral TRD extension of 19% of the stem's circumference.…”
Section: Tree-ring Analysis and Intra-annual Dating Of Eventsmentioning
confidence: 99%
“…3): 1) A passing surge can cause abrasion at the tree stem. The tree reacts to this type of disturbance with changes in its cell structure and the formation of callus tissue as well as tangential rows of traumatic resin ducts (TRD; Stoffel et al, 2005b, c;Perret et al, 2006). 2) The unilateral pressure of the flow can lead to the inclination of the stem and the formation of compression wood on the downslope side of the trunk (Braam et al, 1987;Fantucci and SorrisoValvo, 1999;Stefanini, 2004).…”
Section: Field Methodsmentioning
confidence: 99%
“…However, they suffer from the limited number of available trees or cross-sections (since trees cannot normally be felled in protection forests and stumps of felled trees are not always readily available). With the exception of possibly Perret et al (2005), the term 'frequency' should, thus, be read with caution in these studies. .…”
Section: Later Workmentioning
confidence: 99%
“…Following the procedures described above, Perret et al (2005) analyzed the seasonal timing of events in growth rings of Norway spruce trees on a rockfall slope in the Swiss Prealps (Diemtigtal, Bernese Oberland). Here, seasonal frost prevails and there is no permafrost.…”
Section: Studies On the Seasonal Timing Of Rockfall Activitymentioning
confidence: 99%